Brief intervention to enhance cessation of smokeless tobacco use in newly diagnosed patients with head and neck cancers: A randomized controlled trial in patient-relative dyads - Sai Krishna Tikka; Avinash Shukla; Ripu D. Arora; Sharda Singh; Supriya Mahant; Sachin Verma; Lokesh K. Singh (Indian Journal of Psychiatry)
Introduction: Tobacco use is a major causative factor for head and neck cancers (HNC). Continued use of tobacco even after cancer diagnosis is common and is associated with all-cause and cancer-specific mortality, cancer recurrence and poor treatment response. Evidence suggests that behavioral interventions, help achieve greater smoking cessation rates in HNC patients. However, intervention studies focussed on HNC patients using smokeless tobacco, which is more common than smoking in India, are sparse. Materials and Methods: We conducted a parallel arm randomized controlled trial (RCT) on dyads of patients with recently diagnosed HNC and a close relative. The experimental arm received a brief tobacco cessation intervention (BTCI) and the control arm received treatment as usual (TAU); 27 and 25 dyads in each arm completed the trial. Results: Overall for the dyads using SLT, the relative risk of continuing to use SLT was 3.23 times higher (odds ratio = 7.01) if BTCI was not undertaken at one-month follow-up and 4.43 times higher (odds ratio = 8.65) at 3-months follow-up. For patients only, the relative risk of continuing to use SLT at one-month and 3-months follow-ups was 4.99 and 12.04 times higher, respectively, if BTCI was not undertaken. For relatives only, the corresponding relative risk values were 2.14 and 2.2. Conclusion: We conclude that BTCI delivered to patient-relative dyads, compared to TAU, is effective in enhancing the discontinuation rates of the use of SLT in newly diagnosed patients with HNC. This form of intervention is significantly effective for discontinuing SLT use in the relatives too.